6‐Gingerol Mediates its Anti Tumor Activities in Human Oral and Cervical Cancer Cell Lines through Apoptosis and Cell Cycle Arrest. (7th January 2016) - Kapoor, Vaishali; Aggarwal, Sadhna; Das, Satya N.
Abstract : 6‐Gingerol, a potent nutraceutical, has been shown to have antitumor activity in different tumors, although its mechanism of action is not well understood. In this study, we evaluated antitumor activities of 6‐gingerol on human oral (SCC4, KB) and cervical cancer (HeLa) cell lines with or without wortmannin, rapamycin, and cisplatin. Tumor cell proliferation was observed using 3‐(4, 5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2H tetrazolium, inner salt assay, cell cycle analysis by propidium iodide labeling and flow cytometry, apoptosis by Annexin‐V binding assay, and caspase activity by chemiluminescence assay. 6‐Gingerol showed dose‐dependent cytotoxicity in all three cell lines. Combinations of 6‐gingerol with wortmannin and cisplatin showed additive effects, while with rapamycin, it showed 50% cytotoxicity that was equivalent to IC50 of 6‐gingerol alone. Treatment with 6‐gingerol resulted in G2‐phase arrest in KB and HeLa cells and S‐phase arrest in SCC4 cells. 6‐Gingerol, wortmannin, and rapamycin treatment showed almost two‐fold higher expression of caspase 3 in all cell lines. The results imply that 6‐gingerol either alone or in combination with PI‐3 K inhibitor and cisplatin may provide better therapeutic effects in oral and cervical carcinoma. Thus, 6‐gingerol appears to be a safe and potent chemotherapeutic/chemopreventive compound acting through cell cycle arrest and induction of apoptosis in human oral and cervical tumor cells. Copyright © 2016 John Wiley & Sons, Ltd.